The colouristic paradigm of the novel by M. Kundera «The Farewell Waltz» - Шураєва, Надія Борисівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The functional peculiarities of the colouristics of the novel by M. Kundera «The Farewell Waltz» are considered in the article; the fact that colouristic paradigm has an associative character is ascertained; the semantics, the symbolic fullness and the semantic connections between the main colours are characterized; the ambivalence of the semantic structure of colours (white / blue / red) and colour images (moon, hoop, tablet, nightdress, etc.) is covered; the fact that colour image details reveal the character of personages best of all, reinforcing the message of the work, and the colour component is one of the key markers of the author’s narrative strategy is proved.